Inaccurate age and sex data in the census PUMS files: Evidence and implications - J. Trent Alexander; Michael Davern; Betsey Stevenson (Center for Economic Studies and ifo Institute (CESifo), 2010)
We discover and document errors in public use microdata samples (PUMS files) of the 2000 Census, the 2003-2006 American Community Survey, and the 2004-2009 Current Population Survey. For women and men ages 65 and older, age- and sex-specific population estimates generated from the PUMS files differ by as much as 15% from counts in published data tables. Moreover, an analysis of labor force participation and marriage rates suggests the PUMS samples are not representative of the population at individual ages for those ages 65 and over. PUMS files substantially underestimate labor force participation of those near retirement ages and overestimate labor force participation rates of those at older ages. These problems were an unintentional by-product of the misapplication of a newer generation of disclosure avoidance procedures carried out on the data. The resulting errors in the public use data could significantly impact studies of people ages 65 and older, particularly analyses of variables that are expected to change by age.
Keywords: C80; J10; J20; 330; Current Population Survey; American Community Survey; Census; disclosure avoidance; aging; data; sex; labor force participation; marriage; Mikrozensus; Mikrodaten; Statistischer Fehler; Altersstruktur der Bevölkerung; Geschlecht; USA